Nature of the active phase in hydrodesulfurization: molybdenum carbide supported on activated carbon - Puello Polo, Esneyder; Ayala G., Mónica; L. Brito, Joaquín (CT&F - Ciencia, Tecnología y Futuro, 2014)
This paper studies the effect of the presulfiding agent and the synthesis method on the catalytic activity of thiophene hydrodesulfurization (HDS), using activated carbon supported molybdenum carbides. The catalytic precursor was prepared by co-impregnation of the support with the ammonium heptamolybdate solution. The conventional carbiding consists of a temperature-programmed treatment under a CH4/H2 atmosphere at 1073 K (MC), while the carbothermal method employs pure H2 at 973 K (MCH). The passivated carbides were characterized by X-ray Diffraction (XRD), surface area calculated by the Brunauer–Emmett–Teller multipoint method (BET) and X-ray Photoelectron Spectroscopy (XPS). XRD confirmed the presence of -Mo2C for both methods of synthesis, while specific area were in the order of 400 m2/g. XPS showed the presence at the surface of Moo+ (0 ≤ o ≤ 2), Mo4+ and Mo6+, whose abundance was influenced by used synthesis method with greater proportion of high oxidation states in MCH. Prior to catalytic testing, the passivated carbides were presulfided in situ. HDS tests showed that regardless of the presulfiding agent (H2S or CS2), the carbides obtained by MCH had higher activity than those obtained using the conventional method. The B-Mo2C presulfiding suggests that the carbides with sulfided surfaces or carbo-sulfide mixtures could be the active phase in HDS.